1996
DOI: 10.1016/0014-5793(96)00488-7
|View full text |Cite
|
Sign up to set email alerts
|

The ternary complex of DNase I, actin and thymosin β4

Abstract: Key words: Actin; Thymosin 134; DNase I; Ternary complex; Thiol-specific crosslinking the differently positioned thiol groups in TIM come close enough to distinct thiol groups in actin to allow the formation of crosslinks. In this way two contact sites between the two proteins could be identified, one between the C-terminus of actin (Cys 374) and position 6 of TIM and a second between the )'-phosphate of the actin-bound nucleotide in actin and the sequence 17 28 in TIM.X-ray analysis of monomeric actin took ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
3
9
1
Order By: Relevance
“…These data were confirmed by quantifying total levels of F-actin expression by flow cytometry (Figure 1B, right histogram ), which revealed that gelsolin-EGFP overexpression promoted actin filament severing and decreased the levels of cortical F-actin in CEM.NKR-CCR5 permissive lymphocytes. Our data demonstrate that the functional gelsolin construct and the endogenous gelsolin protein both co-localize with F-actin, in agreement with previous reports describing the binding of gelsolin to actin filaments, even during actin filament processing [20,21]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These data were confirmed by quantifying total levels of F-actin expression by flow cytometry (Figure 1B, right histogram ), which revealed that gelsolin-EGFP overexpression promoted actin filament severing and decreased the levels of cortical F-actin in CEM.NKR-CCR5 permissive lymphocytes. Our data demonstrate that the functional gelsolin construct and the endogenous gelsolin protein both co-localize with F-actin, in agreement with previous reports describing the binding of gelsolin to actin filaments, even during actin filament processing [20,21]. …”
Section: Resultssupporting
confidence: 93%
“…Gelsolin binds to actin filaments with high affinity (Kd of 50 nM) and it is thought to sever actin filaments (reviewed in [14]). After severing, gelsolin remains attached to the barbed ends of the filaments as a cap, thereby preventing the reannealing of actin fragments, and it constitutively co-localizes with the modified actin-filaments [21]. We found that overexpression of functional gelsolin diminished the amount of F-actin in permissive lymphocytes, which had a thinner F-actin cortex than the corresponding controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐linking studies between thymosin‐β4, actin and DNase I have shown that DNase I competes with thymosin‐β4 in binding to actin 19 . In contrast, an earlier report had described the ternary complex between these three components 20 6. depicts the superposition of the DNase I:actin complex onto the β‐thymosin:actin model.…”
Section: Discussionmentioning
confidence: 94%
“…19 In contrast, an earlier report had described the ternary complex between these three components. 20 FIG URE 6 depicts the superposition of the DNase I:actin complex onto the ␤-thymosin:actin model. There is a clear clash between the ␤-thymosin C-terminal helix, and DNase I, which rules out their simultaneous binding to the pointed end of actin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stabilization of antiparallel dimers by certain toxins or proteins of pathogenic origin 51 is likely to underlie their destructive effects on the actin cytoskeleton of the host cell. It remains to be established whether LD form spontaneously under in vivo conditions where the monomer-sequestering proteins thymosin-β 4 and profilin interacting with subdomain 1 of actin [54][55][56] might prevent this type of monomer association by competing for the antiparallel dimer interface.…”
Section: Discussionmentioning
confidence: 98%